MUTATIONS IN PRODUCTION AND APPROPRIATION OF SPACE IN CENTRAL AREAS - Barata-Salgueiro, Teresa (Revista Cidades, 2021)
The production of space is a result of new necessities or demands but simultaneously when creating new features and specializations in the territory, base of new uses, determines and redirects flows producing new centralities. Thus, it imposes new modes of appropriation of space. In this paper we intend to analyse the transformation of the central area focused in the commerce in the light of two contrasting theoretical interpretations, the resilience and the criticism which sees the territory as a social construction. After the introduction of the paper, we briefly present the concept of resilience and the possibility of application to the study of commercial areas. Then we articulate recent transformations of the central areas in terms of commerce and the contribution of the local government intervention for this transformation. To end with a possible interpretation of this process by the two theoretical sets chosen.